Gender-Responsiveness and Its Influence on Gender Equality and Economic Performance of State Colleges and Universities - Ballados, Ma. Teresa B.; Guevarra, Joseph G. (Philippine Social Science Journal, 2020)
State Colleges and Universities (SUCs) are expected to take initiatives to promote gender and development. This study aims to assess gender-responsiveness and its influence on gender equality and the economic performance of SUCs in Negros Occidental, Philippines. The descriptive research design was employed and utilized a researcher-made questionnaire to gather data from randomly selected 36 administrators and 236 employees of SUCs. Using the mean, descriptive results showed high gender responsiveness and a great extent of influence on gender equality and the economic performance of SUCs. Also, the results of the Analysis of Variance and Kruskal-Wallis revealed that significant differences occurred in the level of gender responsiveness and the extent of influence on gender equality among SUCs. Employing Spearman rho, significant relationships were found among gender responsiveness, influence on gender equality, and economic performance. Higher gender-responsiveness may lead to a greater influence on the promotion of gender equality and economic performance.